PRAGMATICS AND ITS ROLE IN TOURISTIC CONTEXT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Globalization has facilitated the development of international tourism. As a result, there has been a significant movement of English language into tourism context. This can be seen from the presence of English, used both in spoken and written discourses in tourism environments to promote iconic landmarks and local cultures. In Uzbekistan, English is the main language, which is used in host-tourist and tourist-tourist spoken interactions. It is also a default language, used in huge numbers of tourism materials such as inflight magazine of Uzbekistan Airways, postcards, guidebooks, like Central Asia Travel and blogs, like Welcome to Uzbekistan.